Artificial Intelligence in Education: Opportunities and Challenges in Improving Learning Efficiency in the Society 5.0 Era - Cecep Sobar Rochmat; Riza Riza; Safitri Anggia Murni (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
The world of education in Indonesia is undergoing a transformation and is ready to welcome the Society 5.0 era. So it offers opportunities and challenges for educators in every educational unit. The purpose of this research is to improve learning efficiency by using AIED-based learning media in the Society 5.0 era. The method used in this research is a qualitative research method with library research data collection techniques. Qualitative analysis was conducted by selecting and examining the latest pedagogical development concepts in the era of society 5.0 and research results from journals in the last five years. If teachers have understood the opportunities and challenges in improving learning efficiency with AIED in the era of Society 5.0. If teachers have understood the opportunities and challenges in improving learning efficiency with AIED in the Society 5.0 era, the world of education will be more developed so that it can produce superior future generations. Teachers must continue to hone their skills regarding general science and technology.